The effect of the COVID-19 pandemic on the stress and depression of nursing students across two countries: a cross-sectional study - Rachel A Joseph; Mala Singh; Kavitha Krishnamoorthy; Khulood Shattnawi; Nahla AlAli; Tracey M. Turner (Academia Mental Health & Well-Being)
The COVID-19 pandemic brought significant stress to nursing students when the global lockdown resulted in immediate changes to the method of delivery or complete cessation of education. The purpose of this study was to assess the stress of nursing students, identify associations between stress scores and sociodemographic variables, and compare the experience of nursing students in multiple sites in India and Jordan. A non-experimental, exploratory, cross-sectional research design was employed to investigate the experiences of nursing students recruited from Jordan and India. This study utilized sociodemographic data, the Impact of Events Scale-Revised (IES-R) to measure stress levels, the Center for Epidemiologic Studies Depression (CES-D) scale to screen for depressive symptoms, and the bipolar scale to assess coping behaviors. Descriptive statistics, independent samples t-tests, and regression analysis were performed. Of the 1875 participants, 1504 were aged 18–25 years, and 1313 were females. In total, 54.67% of participants exhibited CES-D total scores indicative of depression. A significant difference in CES-D scores between the Indian and Jordanian groups was found (independent samples t-test, t(1873) =−7.79; p < 0.001), rejecting the null hypothesis. The mean IES-R total score of 40.42 indicated potential post-traumatic stress disorder. Additionally, a significant difference in IES-R scores between non-Jordanian and Jordanian groups was observed (t(349.28) = −20.78; p < 0.001). Nursing students from middle-income countries like India and Jordan faced significant challenges during lockdowns due to limited social support and academic resources. To mitigate these impacts, targeted guidance, support, and counseling are crucial. Self-care initiatives and emotional support for nursing students can benefit the current and future students who have faced challenges during the pandemic before entry to the nursing program. Nursing faculty can play a pivotal role by implementing mentorship programs to identify and assist at-risk students.